Opportunities for Adaptation of the Smart City Concept – A Regional Approach - Nagy, Zoltán; Tóth, Géza; Szendi, Dóra (Theory, Methodology, Practice – Review of Business and Management, 2016)
Smart City applications are becoming more prevalent in the world’s major cities. In this study we briefly introduce the essence of this concept and attempt to examine the basis for introduction of the concept subsystems in Northern Hungary. We found that the region under investigation significantly lags behind the national average in the case of indicators for quantifying Smart City applications. We identify areas with a particularly low score on the newly developed SMART index and propose a possible area for future intervention.